DNA transport in bacteria. - Errington, J; Bath, J; Wu, L (2001)
DNA transport is important in various biological contexts--particularly chromosome segregation and intercellular gene transfer. Recently, progress has been made in understanding the function of a family of bacterial proteins involved in DNA transfer, and we focus here on one of the best-understood members, SpoIIIE. Studies of SpoIIIE-like proteins show that they might couple DNA transport to processes such as cell division, conjugation (mating) and the resolution of chromosome dimers.